The M/M/1/K interdependent retrial queueing model with impatient customers and controllable arrival rates - Antline Nisha, B.; Thiagarajan, M. (International Journal of Applied Mathematical Research, 2014)
In this paper an M/M/1/K interdependent retrial queueing model with controllable arrival rates and impatient customers is considered. The steady state solutions and the system characteristics are derived for this model. The analytical results are numerically illustrated and the effect of the nodal parameters on the system characteristics are studied and relevant conclusion is presented.Keywords: finite capacity, interdependent primary arrival and service processes, impatient customers, retrial queue, single server.